EFFORTS OF BHABINKAMTIBMAS THROUGH COUNSELING AND EDUCATION TO THE COMMUNITY IN THE JURISDICTION OF THE KENDAL POLICE IN PREVENTING THE ABUSE AND CIRCULATION OF DRUGS - KARINA VIKTORIA ANAMI (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS OF BHABINKAMTIBMAS THROUGH COUNSELING AND EDUCATION TO THE COMMUNITY IN THE JURISDICTION OF THE KENDAL POLICE IN PREVENTING THE ABUSE AND CIRCULATION OF DRUGS Karina viktoria anami, 18,231 Karinaviktoria03@gmail.com The background of this problem arises because guidance and counseling have been carried out, but drug abuse and circulation still occurs, this paper aims to describe the performance and efforts of bhabinkamtibmas through coaching and counseling the community in the Kendal police jurisdiction in preventing drug trafficking and abuse. At this writing the author uses a qualitative approach with data collection techniques by interviewing, observing and studying documents. Sources of data used are primary data and secondary data. Data validity uses data triangulation. Data analysis techniques are data reduction, data presentation, conclusion drawing/verification. The concepts and theories used to analyze the focus of this research are the concept of coaching and counseling, the concept of bhabinkamtibmas, the concept of drug trafficking and abuse. While the theory used is POAC management theory, elements of management theory, cooperation theory, and communication theory. Bhabinkamtibmas is placed in each police station to oversee villages in the police station to carry out guidance and counseling. Keywords: Efforts, Bhabinkamtibmas, coaching and counseling, drug abuse and distribution.